2014
DOI: 10.1007/s10853-014-8608-2
|View full text |Cite
|
Sign up to set email alerts
|

A 3D micromechanical study of deformation curves and cell wall stresses in wood under transverse loading

Abstract: The deformation of wood is analyzed using the finite element method to quantify the phenomena in wood cells and cell walls. The deformation curves of computed microstructures are compared to experimental observations in two different loading cases: compression and combination of shear and compression. Simulated and experimental shapes of deformation curves match qualitatively and the deformation shapes exhibit a similar response to change in the loading mode. We quantify the intra-cell-wall stresses to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Latewood showed flattening of the cell and lateral expansion of the cells up to 35 % strain and s-shape deformation of the cell wall above 35 % strain. Recently, the same experimental deformations were evidenced in microFEM simulations by Fortino et al (2015). Tabarsa and Chui (2000) studied the stress-strain behaviour of earlywood and latewood during radial compression.…”
Section: Earlywood and Latewood Properties And Compression Mechanismssupporting
confidence: 52%
“…Latewood showed flattening of the cell and lateral expansion of the cells up to 35 % strain and s-shape deformation of the cell wall above 35 % strain. Recently, the same experimental deformations were evidenced in microFEM simulations by Fortino et al (2015). Tabarsa and Chui (2000) studied the stress-strain behaviour of earlywood and latewood during radial compression.…”
Section: Earlywood and Latewood Properties And Compression Mechanismssupporting
confidence: 52%
“…The results showed that the cells collapse and undergo different deformation patterns as a result of compressive load. In a recent study by Fortino et al (2015), a bundle of wood cells was modelled with square and hexagonal shapes to study cell wall stresses under transverse loading. The authors found out increasing values of cell angles cause decreasing stress levels at the same deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main cause for the boundary effects along the edges of the test specimens are the inhomogeneous internal structure (cross section assembly) of the test specimens and the influences of the annual ring orientation. The influences of the cell structure, discussed in detail in Fortino et al (2015), are not directly investigated, they are implicitly considered in the determination of the orthotropic shrinkage and swelling coefficients depending on the assembling of the crosssection (layers longitudinal and transverse).…”
Section: Analysis Of Boundary Effectsmentioning
confidence: 99%